Technical report: solving two dimensional explicit heat conduction equation by using finite difference method / Aimi Zafirah Mat Nawi, Fatin Munirah Azizul and Maryam Nadhrah Mohamad Tarmizi - Mat Nawi, Aimi Zafirah; Azizul, Fatin Munirah; Mohamad Tarmizi, Maryam Nadhrah (2017)
A Laplace's heat conduction equation is derived and then solved before identifying the temperature distribution of aluminium using the same equation. The heat conduction equation was derived from the First Law of Thennodynamics before applying Fourier's Law of Heat Conduction and then solved using central finite difference method and Gauss-Seidel iterations. The temperature distribution of aluminium was calculated using a different set of boundary equations than the one used for the first heat equation. Three different number of nodes, 2x2, 3x3 and 8x8 were used to solve the heat equation to see how it affected the accuracy of the temperature distribution. The solution then was graphed using MATLAB software. It was found that the more nodes used, the more accurate the temperature distribution calculated. All the results gained were compared with previously published work for validation.